Islamic Perspective in Viewing the Meaning of Cost - Muhamad Rifki Botutihe Botutihe Uno; Niswatin; Ronald S. Badu (International Journal of Religious and Cultural Studies, 2023)
This study uses an Islamic phenomenology approach to understand the meaning of business cost from an Islamic perspective. The Kauniyah (Natural Phenomena) verses were explored through business actors as informants, they are the owner of Sama Jaya and the owner of Karsa Utama, while the Qauliyah (the words of Allah in the Qur’an) verses were explored through the Al-Qur’an interpreting scholar and Hadith scholars. The research demonstrates that the cost in an Islamic context refers to the sacrifice of Allah's servant in order to provide benefits and bring blessings because they are considered as necessities. Costs are also viewed as benefits because they can provide welfare, both material and non material to employees with the aim of bringing blessings from Allah. This is believed to a promise as stated in the Al-Qur’an in Surah As-Saff verses 10-11 that real sacrifice is a sacrifice that can bring the love of Allah.